Investment attractiveness of Republic of Crimea and its assessment - I. N. Primyshev (Омский научный вестник: Серия "Общество. История. Современность")
In the article, the author calculated the value of the investment attractiveness index for the subjects of the Russian Federation that are part of the southern Federal district. A SWOT analysis of the investment attractiveness of the Republic of Crimea is conducted. Measures aimed at implementing the investment development of the Republic of Crimea are proposed. The analysis of the structure of the gross regional product by type of economic activity is carried out. It is revealed that the largest share in the structure of the regional economy falls on the industrial complex of the Republic of Crimea. The main tasks and measures for the strategic development of the industrial complex of the Republic of Crimea are defined. Assessing the investment attractiveness of the region is of interest to authorities, investors and local business communities